Unmet psychological needs underlying mobile phone dependence among medical undergraduates: a qualitative study based on the basic psychological needs theory - Chen, Jun; Guo, Yanxia; Huang, Ruiyu; Liu, Gang; Zhang, Baolu (Frontiers in Psychology, 2025)
BackgroundMobile phone dependence is recognized as a global public health concern, particularly among medical students. The unmet psychological needs reflected in mobile phone dependence among undergraduate medical students remain unclear. Our study aimed to explore the unmet psychological needs underlying mobile phone dependence among medical undergraduates from the Basic Psychological Needs Theory (BPNT) perspective through interviews.MethodsFifteen undergraduate medical students exhibiting mobile phone dependence were recruited through purposive sampling for in-depth, semi-structured interviews at a medical university in China. Data were analyzed using Braun and Clarke’s deductive thematic analysis method.ResultsOur study identified four main themes and nine subthemes. The four main themes are (1) autonomy, which includes low self-regulation, reality pressure evasion, and negative affect; (2) competence, which includes achievement through mobile applications and effects on social performance abilities; and (3) relatedness, which includes social network maintenance and digital medical identity formation, (4) meaning in life, which includes life direction confusion and value confusion. Notably, 46.7% of participants identified relatedness needs as the dominant factor in their mobile phone dependence.ConclusionOur study uniquely found that mobile phones serve as tools for medical students to compensate for unmet basic psychological needs, manifested as pressure evasion, achievement-seeking, and professional identity construction, while also revealing meaning in life that extends beyond the BPNT frameworks. Our study recommends that medical schools provide autonomy-supportive environments, create opportunities for skill verification through EPA-based assessments and simulations, and establish mentoring systems with digital platforms for professional development. School psychologists and counselors should implement evidence-based interventions like mindfulness training and group self-regulation programs to foster healthy mobile phone usage.